Hubungan Pola Asuh Orangtua Dengan Perilaku Seksual Remaja Di Sma Tri Bhakti Pekanbaru - Raja Pieba Aguma; Ari Pristiana Dewi; Darwin - Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research was determine the relationship between parenting parentswithadolescentsexualbehaviorinSMA TriBhaktiPekanbaru. This research used adescriptive correlationmethodwith cross sectional study. This research was conductedon177adolescentsinSMATriBhaktiPekanbaruusingstratified random sampling technique. The instrument used was a questionnaire parenting parents 18 questionsandadolescent sexualbehaviorquestionnaire13questions.The analysis usedunivariateandbivariateanalysis. The resultsof chi-squaretestp value=0.001, wecanconcludetheexistenceofa relationshipbetweenparentingparentswithadolescentsexualbehavior inSMATriBhaktiPekanbaru. Expected from the results of this research can be input in a broader research by increasing the number of samples, appendthe locationas well asonother factorsthatmayaffectadolescent sexual behavior. Keywords: Parenting parents, sexual behavior, teenagers